The Delivery and Activation of Growth Factors Using Nanomaterials for Bone Repair - Yiwei Li; Chun Xu; Chang Lei (MDPI AG, 2023)
Bone regeneration is a comprehensive process that involves different stages, and various growth factors (GFs) play crucial roles in the entire process. GFs are currently widely used in clinical settings to promote bone repair; however, the direct application of GFs is often limited by their fast degradation and short local residual time. Additionally, GFs are expensive, and their use may carry risks of ectopic osteogenesis and potential tumor formation. Nanomaterials have recently shown great promise in delivering GFs for bone regeneration, as they can protect fragile GFs and control their release. Moreover, functional nanomaterials can directly activate endogenous GFs, modulating the regeneration process. This review provides a summary of the latest advances in using nanomaterials to deliver exogenous GFs and activate endogenous GFs to promote bone regeneration. We also discuss the potential for synergistic applications of nanomaterials and GFs in bone regeneration, along with the challenges and future directions that need to be addressed.